Perkaderan Intelektual Pimpinan Cabang Ikatan Mahasiswa Muhammadiyah Kabupaten Sukoharjo - Lestari, Muflihah Dwi; , Rina Trisnawati, Dra., M.Si., Akt., Ph.D (2017)
This research purpose is to describe intellectual cadre training in Muhammadiyah Students Association of Sukoharjo. This research is a qualitative field research. Object of this research is an intellectual cadre training of Muhammadiyah Students Association of Sukoharjo. Techniques of collecting data in this research are observation, interview and documentation. Data analysis in this research is a qualitative descriptive analysis. This finds reaserch that there are two kinds of intellectual cadre trainings: main training and supportive one. The main training is either Baret Merah activity or Sukoharjo Intellectual School (SIS), while the supportive training is discussion. There are three applied methods in this intellectual cadre training, they are Focus Group Discussion (FGD), presentation and exercise. The implementation of the intellectual cadre training have supportive factors and obstacle factors. The supportive factors contain internal and external ones. The internal supportive ones are: (1) movement orientation in building Muhammadiyah Students Association focuses on intellectualism; (2) Condition of Muhammadiyah Students Association that has intellectual visior and mission, and also discussion habit. The supportive factor of Muhammadiyah Students Association is support from resignation of cabinet, Muhammadiyah institution. The obstacle factors of the intellectual cadre training of Muhammadiyah Students Association are (1) inconsistensy of committee with the job descriptions which become their responsibility; until effect to the concept which had been arrange doesnot better. (2) there are chiefs or cadres who are not interested in intellectual activity; (3) the money problem becomes something that is enough yet because Muhammadiyah Students Association still depends on the others.